L’inscription paradoxale du dispositif Diwan en Bretagne - Maryvette Balcou-Debussche; Frédéric Tupin (Éducation et Socialisation)
This contribution questions the social inscription of the bilingual Diwan scheme in Britain, nearly 40 years after the early stages of a project that defends the choice of a total immersion in the Breton language, in a regional context where the number of ‘natural’ speakers continues to decline. Viewed in its dimensions "soilless", the educational intervention is questioned here through its psychosociological, organizational, institutional and social dimensions. The analyses are grounded on 48 semi-structured interviews with management teams, teachers, students and parents, as well as in situ observations in 10 schools. The results help to highlight the basis on which the Diwan scheme was built, but they also point out tensions and debates, regarding the actions and the actors as well as the priorities they expressed.